Jews and the Ends of Theory - Bush, Andrew; Wolfson, Elliot R.; Hever, Hannan; Geller, Jay; Boyarin, Jonathan; Porter, James I.; Jay, Martin; Land, Martin; Land, Martin; Dolgopolski, Sergey; Hammerschlag, Sarah; Ginsburg, Shai P.; et al. (Fordham University Press, 2018)
Frontmatter -- Contents -- Introduction. Jews, Theory, and Ends -- chapter 1. Leo Lowenthal and the Jewish Renaissance -- chapter 2. The Palestinian Nakba and the Arab-Jewish Melancholy: An Essay on Sovereignty and Translation -- chapter 3. The Ends of Ladino -- chapter 4. The Last Jewish Intellectual: Derrida and His Literary Betrayal of Levinas -- chapter 5. Jews, in Theory -- chapter 6. The Jewish Animot: Of Jews as Animals -- chapter 7. The Off-Modern Turn: Modernist Humanism and Vernacular Cosmopolitanism in Shklovsky and Mandelshtam -- chapter 8. Old Testament Realism in the Writings of Erich Auerbach -- chapter 9. Buber versus Scholem and the Figure of the Hasidic Jew: A Literary Debate between Two Political Theologies -- chapter 10. Against the “Attack on Linking”: Rearticulating the “Jewish Intellectual” for Today -- 11. Recovering Futurity: Theorizing the End and the End of Theory -- Contributors -- Index